Inventando a Africa do Sul em imagens: Uma análise da série Shaka Zulu (1986) - SILVA, Milca Salém dos Santos (2022)
This paper suggests to problematize, contextualize and transform into an object of historical analysis the invention of Shaka kaSenzangakhona in the homonymous audiovisual series, Shaka Zulu (1986), by the South African Broadcasting Corporation (SABC). The interest we have in this series is justified by the fact that Shaka Zulu (1986) is an audiovisual product with historical implications, and one that is still the subject of much debate in historiography. The plot was written by an American, Joshua Sinclair, and directed by South African William C. Faure in a period when South Africa, under the Apartheid regime, suffered a cultural embargo from other African, Latin American, and European countries. This "hindered" the export of South African audiovisual productions. The series is divided into ten episodes that tell the story of Shaka, Zulu Emperor, who lived from 1787 to 1828. Shaka is recognized as one of the most feared and important leaders in the history of southern Africa, responsible for modernizing the military practices of the Zulu Kingdom, which would become decades later a symbol of resistance to British colonization. This study aims to recover the idea defended by Jacques Rancière (1998) about the two existing ways of relating "cinema [audiovisual] and history," where he says that this relationship should be constituted as a result of the transformation of one of the terms into the object of the other: history as the object of cinema, or cinema as the object of history (Rancière, 1998). In the case of the audiovisual series Shaka Zulu (1986), our object of research, it can be seen that, by having transformed history into its cinematographic object, it ended up also becoming an object of history because of the tensions and ruptures it raised in the national and international debates after its worldwide release.